PERBEDAAN HASIL BELAJAR PAI DITINJAU DARI GENDER SISWA KELAS VIII DI SMPI ALMAARIF 01 SINGOSARI - M Miftahul Fadilah; Ika Ratih Sulistiani; Muhammad Sulistiono (Vicratina : Jurnal Ilmiah Keagamaan, 2019)
This research has the main purpose, it is distinguishing PAI learning outcomes in terms of the gender of class VIII students at SMPI Almaarif 01 Singosari 1. The researcher used a quantitative method by asking for value data from the teacher of PAI class VIII. In this study, the researcher also conducted an interview with the head of the School and the teacher of PAI class VIII. The sample used in the study was class VIII A-H. The number of samples is 234 students which are divided into 2 groups. Likewise the remaining 4 male students with the same number 117 students. The data collection conducted by researchers is only taking documentation. The data analysis technique used by researchers is the t-test. On the results of the t-test, there were significant differences between the female student class and the male student class. after t test with the help the SPSS 24 program for windows, the average of female class student learning outcomes was 80.67, while the average for male class students was 78.13. It can be concluded from the results of this research that there is a difference in learning outcomes between female students and male students, and the learning outcomes of female class students are higher than male class students